ε-Closed Sets: Talal Al-Hawary - Team, Support (Thai Journal of Mathematics, 2018)
Our goal in this paper is to introduce the relatively new notions of ε -closed and ε -generalized closed sets. Several properties and connections to other well-known weak and strong closed sets are discussed. ε -generalized continuous and ε-generalized irresolute functions and their basic properties and relations to other continuities are explored.